From definition to protection: dilemmas and reflections on the right to refuse treatment for patients with mental disorders in Chinese mainland - Li, Xiaofu; Li, Xiaofan (Frontiers in Public Health, 2024)
The right to refuse treatment is still a very unfamiliar concept in theory and practice in Chinese Mainland. It is still questionable whether the relevant laws confirm this right of mental patients. In practice, there is actually a negative attitude towards the right of hospitalized patients with mental disorders to refuse treatment. Based on respect for the autonomy and health rights of patients with mental disorders, the patients’ right to refuse treatment should be confirmed and corresponding legal protection should be provided for this right. A more feasible approach would be to set up an internal review mechanism as a means of protecting the right to compulsory medical treatment of patients with mental disorders.